2021
DOI: 10.1186/s13256-021-02960-w
|View full text |Cite
|
Sign up to set email alerts
|

Primary leiomyoma of the ureter: a case report

Abstract: Background Only 14 cases of leiomyoma with ureteral origin have been reported previously. Such primary leiomyomas often present as hydronephrosis, making the diagnosis difficult. Radical nephroureterectomy is often performed because of the possible diagnosis of a malignant tumor. We report the 15th case of primary leiomyoma with a ureteral origin. Case presentation A 51-year-old Japanese man presented with a chief complaint of asymptomatic gross he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The return of urea and creatinine values for this patient to species reference ranges after the procedure reflects the impact on the functional reserve of the previously affected kidney. Similarly, in humans, although upper urinary tract tumors are also rare [31][32][33], it was reported that malignant ureteral tumors can be cured by local resection [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…The return of urea and creatinine values for this patient to species reference ranges after the procedure reflects the impact on the functional reserve of the previously affected kidney. Similarly, in humans, although upper urinary tract tumors are also rare [31][32][33], it was reported that malignant ureteral tumors can be cured by local resection [34][35][36].…”
Section: Discussionmentioning
confidence: 99%